Angle dependent synchrotron X-ray absorption spectroscopic structural studies on Ba0.85Ca0.15Zr0.1Ti0.9O3 ferroelectric ceramics. (November 2020) - Munthala, Dhanunjaya; Sonklin, T.; Buatip, N.; Pomyai, P.; Amonpattaratkit, P.; Klysubun, W.; Pojprapai, Soodkhet
Abstract: Synchrotron X-ray absorption near edge structure (XANES) technique was employed to investigate the local structure, domain orientation, and Ti off-center displacement in unpoled and poled barium calcium zirconate titanate (BCZT) ceramics. The angular periodicity of domain orientation found to be 180° in poled ceramic and random nature in an unpoled ceramic. The experimental XANES spectra of peak B and E showed sine square dependent and opposite behavior. X-ray Diffraction (XRD), hysteresis loop ( P-E ), and strain hysteresis loop ( S-E ) loop results confirm the existence of morphotropic phase boundary (MPB) and domain orientation. The asymmetry in the strain loops tells about the ferroelectric switching of domains after poling. The minimum value of Ti off-center displacement at 60° tells about the preferential orientation of domains after poling. XANES thereby demonstrates the quantitative and qualitative analysis of domain orientation and Ti off-center displacement in ferroelectric ceramics. Graphical abstract: Image, graphical abstract